Yersinia enterocolitica serotype O:3 alters the expression of serologic HLA-B27 epitopes on human monocytes. - Wuorela, M (1997)
The expression of serologic HLA-B27 epitopes on leukocytes of patients with reactive arthritis or ankylosing spondylitis has been shown to be modified in the course of the disease. The purpose of this work was to study whether phagocytosis of arthritis-triggering microbes in vitro alters the expression of HLA-B27 molecules on human antigen-presenting cells and to characterize the underlying mechanisms. Human monocytes and HLA-B27- or HLA-A2-transfected human U-937 cells were exposed to Yersinia enterocolitica serotype O:3. The expression of different epitopes of HLA-B27 was monitored by using immunofluorescence, and their synthesis was determined by quantitative immunoprecipitation. Our results show that phagocytosis of Y. enterocolitica serotype O:3 changed the expression of serological HLA-B27 epitopes. This was due to the reduced synthesis of HLA-B27 molecules. The expression of especially the epitopes which depend on the presence of peptides in the antigen-binding groove was changed. The expression of the ME1 epitope, which has been shown to be important for T-cell recognition in patients with reactive arthritis, was decreased. Down-regulation of epitopes important for the T-cell recognition may impair the elimination of arthritis-triggering microbes and lead to persistent infection. In addition, Y. enterocolitica serotype O:3 seemed to alter the repertoire of peptides presented by the HLA-B27 molecules on human monocytes. This may have a role in the pathogenesis of reactive arthritis via an autoimmune mechanism.